Personal Selling Communication Strategy of Oemah Tahu Purwokerto for Increasing Brand Awareness Through Entrepreneurial Tourism Program - Aliyyah, Hanifah Nur; Turistiati, Ade Tuti; Sari, Rida Purnama (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
The level of competition in the culinary world is becoming increasingly competitive, making marketing activities highly necessary for various culinary business actors, including Oemah Tahu Purwokerto, to enhance brand awareness through entrepreneurial tourism programs. This study aims to identify and analyze the personal selling communication strategies implemented by Oemah Tahu to increase brand awareness through entrepreneurial tourism programs. The research method used is descriptive qualitative, utilizing the Elaboration Likelihood Model theory by Richard E. Petty and John T. Cacioppo. Data collection techniques include observation, in-depth interviews, and documentation studies. The research results show that Oemah Tahu uses personal selling to directly promote their products and programs to potential customers. This strategy is effective in creating closeness, benefiting both parties and achieving the level of brand recall. These findings are related to the Elaboration Likelihood Model theory, where the majority of informants prioritize the clarity of the message content through Central Route Processing, which is more dominant and important compared to Peripheral Route Processing.